2008
DOI: 10.1111/j.1939-1676.2008.0073.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Usefulness of Blood Leukocyte Changes in Canine Parvoviral Enteritis

Abstract: Background: Despite treatment, many dogs still die of complications related to canine parvoviral (CPV) enteritis. Effective prognostication would be beneficial in managing this disease.Hypothesis: We hypothesize that the occurrence of leukocytopenias at admission and at 24 and 48 hours after admission, and changes in absolute leukocyte counts over time, could be used to predict outcome.Animals: Sixty-two puppies with confirmed CPV. Methods: A prospective study was performed. CBC was performed daily until disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 14 publications
10
72
1
16
Order By: Relevance
“…In this study, hematological findings including leukopenia, lymphopenia, monocytopenia and granulocytopenia in non-survival puppies were similar to those of previous studies (8,39).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, hematological findings including leukopenia, lymphopenia, monocytopenia and granulocytopenia in non-survival puppies were similar to those of previous studies (8,39).…”
Section: Discussionsupporting
confidence: 77%
“…Canine parvovirus (Parvoviridae type 2a and 2b) has a predilection to infect rapidly dividing cells of the gastrointestinal tract, lymphoid tissue, and bone marrow, leading to hemorrhagic diarrhea, vomiting, marked leukopenia, and immunosuppression (8). Bacteriemia leads to sepsis in dogs with immunosuppression (4,6,16,25,29,37).…”
Section: Introductionmentioning
confidence: 99%
“…Results of 1 study 14 indicated that an accurate prognosis could be obtained for puppies with CPV enteritis at 24 hours after admission by evaluating changes in blood leukocyte concentrations. Investigators in another study 7 found that CPV-infected puppies that have lymphopenia and hypoalbuminemia at admission are hospitalized for longer periods, compared with puppies without these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed to investigate potential prognostic markers in dogs infected with CPV, which include endocrine, 13 hematologic, 14 and biochemical variables. 7,15 In human patients with severe sepsis, mortality rates may exceed 30%, despite advanced supportive care 16 ; these results are similar to those of studies in which mortality rates of 15% 17 to 53% 15 were found for parvovirus-infected puppies that received aggressive supportive care.…”
Section: Small Animals/ Exoticmentioning
confidence: 99%
“…A leucopenia pode estar relacionada à ação de vírus (principalmente parvovírus) sobre as células hematopoiéticas precursoras de vários leucócitos. Pode ser determinada, também, por perda massiva de leucócitos pela parede intestinal (GODDARD et al, 2008). O tratamento tradicional instituído para os cães do estudo foi realizado de acordo com a literatura (SWANGO, 1997;LOPES et al, 2015) e foi efetivo na maioria dos animais já que o índice de recuperação nos dois grupos foi de 65%, semelhante ao relatado na literatura (LOPES et al, 2015).…”
Section: Resultsunclassified